Digital Learning Workshops for Elementary Teachers in MIS Al-Fikri Kampung Pajak - Tin Sukaisih (Rahis Cendekia Indonesia, 2024)
This article reports on a community-based digital learning workshop program conducted for elementary teachers at MIS Al-Fikri Kampung Pajak. The program aimed to improve teachers’ digital literacy and integrate technology into their teaching practices to enhance student engagement and learning outcomes. Using a qualitative descriptive approach, the study involved 12 teachers who participated in three workshop sessions covering basic computer skills, educational platforms like Google Classroom and Canva, and multimedia integration. Data collected through observations, questionnaires, and interviews revealed significant improvements in teachers’ confidence and ability to use digital tools. The workshops also fostered greater collaboration among teachers and maintained alignment with Islamic educational values by encouraging the incorporation of religious content into digital materials. Challenges such as limited infrastructure were noted, highlighting the need for sustained support. The study concludes that tailored digital training can empower teachers in rural Islamic schools to innovate their teaching while preserving their cultural and religious identity